The Influence Of Financial Literacy And Familiarity Bias On Investment Decisions Of Yogyakarta Investors On Digital Investment Platforms - Muhammad Reynaldi; Sri Mulyati (Cita konsultindo, 2024)
This study aims to investigate the influence of financial literacy and familiarity bias on investment decisions in the capital market. A quantitative approach was utilized, with data collected via an online questionnaire from 235 respondents with investment experience, residing in Yogyakarta. Data analysis was performed using Structural Equation Modelling (SEM) through SmartPLS 4 software. The results indicate that financial literacy has a significant positive effect on investment decisions, and familiarity bias was found to positively affect investment decisions as well. These findings underscore the importance of enhancing financial literacy to promote more informed investment decisions, while also addressing the influence of familiarity bias, which may impede the optimization of investment portfolios. The implication is that financial literacy improvement should be a key focus for financial institutions and policymakers to enhance the quality of investment decisions within the public.